Crosslinking diene rubbers by using an inverse vulcanised co-polymer. Issue 21 (12th October 2020) - Wang, Dong; Tang, Zhenghai; Liu, Yinjun; Guo, Baochun
Abstract : A green approach is explored in crosslinking diene rubbers by using an inverse vulcanised co-polymer of sulfur and styrene. Abstract : Crosslinking of diene rubbers by the traditional sulfur-based curing package inevitably utilizes toxic activators and accelerants, which causes potential dangers and environmental pollution. Herein, we report on the rapid synthesis of sulfur co-polymers by inverse vulcanization of S8 and styrene through a nucleophilic activation mechanism and demonstrate that the inverse vulcanised co-polymer is highly efficient in crosslinking diene rubbers in a green manner. Compared with the traditional sulfur-cured counterpart, the sulfur co-polymer-cured sample with an identical crosslinking density exhibits a remarkably larger breaking strain and a higher elasticity.